Identification of Flavonoids in the Fruit of Cassia fistula by High Performance Liquid Chromatography-Electrospray Mass Spectrometry - Jain*, Rahul; Chaurasia, Sangeeta; Saxena, R.C.; Jain, D.K. (Asian Journal of Chemistry, 2011)
Cassia fistula is traditionally known for its medicinal properties. It contains many phenolic compounds that may have potential as antioxidant. High performance liquid chromatography coupled with electrospray mass spectrometry (LC-ESI/MS) was used for the identification of flavonoids in the fruit of Cassia fistula. Mobile phase used in the chromatographic separation was 2 mM ammonium acetate buffer (solvent-A, pH 2.5 with acetic acid) and acetonitrile (solvent-B) with gradient programming. The peaks were identified by the comparison of retention time, UV-vis spectroscopic and mass spectrometric data with authentic standards and/or literature data. The identified flavonoids included two anthocyanins (cyanidine-3-O-galactoside, petunidin-3-O-glucoside), two flavan-3-ols (catechin and epicatechin) and one flavonol glycoside (kaempferol-3-O-glucoside).